Pengaruh Qaulan Kariman dalam Meningkatkan Kualitas Hubungan Antar Individu - Sucipto, Adi; Azhar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to determine the influence of qaulan kariman in improving the quality of relationships between individuals. This research This research uses a descriptive method with a qualitative approach, this research is field in nature. In this approach, researchers involve collecting diverse data, such as interviews, observations, and documents, as well as holistic and contextual data analysis. This research uses primary data sources in the form of observation results and secondary data sources in the form of literature reviews. In collecting data, researchers carry out non-participant observations which are carried out by indirectly observing natural behavior, activities and research objects. The data analysis technique in this research was carried out by reducing data, presenting data, and making conclusions. The results of this research show that the implementation of qaulan kariman is not only an ethical norm, but also the basis for building a community of mutual support and improving mutual prosperity. By maintaining good words, individuals can create relationships that are healthy, harmonious, and based on the values of truth and virtue. This ensures that communication serves as a means to strengthen bonds, create peace, and build a society based on positive values.